2023
DOI: 10.1186/s13643-023-02314-1
|View full text |Cite
|
Sign up to set email alerts
|

Community capacity for prevention and health promotion: a scoping review on underlying domains and assessment methods

Vera Birgel,
Lea Decker,
Dominik Röding
et al.

Abstract: Background Building community capacity is an essential health promotion approach, which refers to the characteristics of communities that affect their ability to identify and address social and public health problems. Despite general agreement about certain capacity domains and frameworks, there is no comprehensive and consistent assessment of community capacity. Therefore, the aim of this scoping review is to identify the domains and methods used to assess community capacity related to communi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…The study used ten domains to assess community capacity for prevention and health promotion, identified through a scoping review ( Birgel, Decker, et al, 2023 ). Based on the definitions of these domains, items from the Community Key Informant (CKI) were identified that allowed measurement of each domain or dimensions of the domain, notwithstanding that the CKI was not originally designed for comprehensive community capacity assessment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study used ten domains to assess community capacity for prevention and health promotion, identified through a scoping review ( Birgel, Decker, et al, 2023 ). Based on the definitions of these domains, items from the Community Key Informant (CKI) were identified that allowed measurement of each domain or dimensions of the domain, notwithstanding that the CKI was not originally designed for comprehensive community capacity assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the present analyses, the validity and reliability of the community capacity scales was evaluated, as described in Birgel, Walter, & Röding, 2023 . Structural validity of the ten capacity constructs was investigated through an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La salud pública es un aspecto emergente en los últimos años, ha surgido la necesidad de crear herramientas con el fin de empoderar a las comunidades para obtener una perspectiva multinivel sobre los problemas de salud para desarrollar estrategias efectivas de promoción de la salud y prevención de la enfermedad, ya que los métodos tradicionales suelen ser insuficientes. (1) Una de las herramientas más utilizadas para evaluar este tipo de las capacidades comunitarias es el "The Community Capacity Building Tool". (2) Está diseñada como herramienta de planeación aplicada a los proyectos de promoción en salud, donde permite identificar fortalezas, debilidades y progreso del proyecto, y así dirigir el rumbo de las intervenciones.…”
Section: Introductionunclassified
“…As such, we conducted a scoping review in which we identified domains emphasized for prevention and health promotion prior to this study: community participation, knowledge & skills, resources, leadership, community power, sense of community, collaboration, critical awareness & problem-solving, and community structure. This scoping review provides definitions for each of the capacity domains (Birgel et al 2023).…”
Section: Introductionmentioning
confidence: 99%